2018
DOI: 10.1200/jgo.17.00151
|View full text |Cite
|
Sign up to set email alerts
|

Financial Impact of Complex Cancer Surgery in India: A Study of Pancreatic Cancer

Abstract: PurposeThe rapidly increasing burden of cancer in India has profound impacts on health care costs for patients and their families. High out-of-pocket (OOP) expenditure, lack of insurance, and low government expenditure create a vicious cycle, leading to household impoverishment. Complex cancer surgery is now increasingly important for emerging countries; however, little is understood about the macro- and microeconomics of these procedures. After the Lancet Oncology Commission on Global Cancer Surgery, we evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 34 publications
(34 reference statements)
1
23
0
Order By: Relevance
“…The systematic review identified 3639 records, of which 105 full-text studies were retrieved [ 8 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ,…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The systematic review identified 3639 records, of which 105 full-text studies were retrieved [ 8 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ,…”
Section: Resultsmentioning
confidence: 99%
“…However, this study had a small sample size and contributed relatively little to the estimated 42% weighted average income spent as out-of-pocket expenses in LMICs. Additionally, four studies defined explicit thresholds for catastrophic health expenditure [ 27 , 68 , 69 , 101 ]. They defined a threshold of annual income spent as out-of-pocket expenditures and estimated the proportion of patients exceeding it.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations